Brazilian Local Government Performance: Politics or Managerial Quality? - Gomes, Ricardo Corrêa; Avellaneda, Claudia Nancy (Organizações & Sociedade, 2017)
<!--[if gte mso 9]> Normal.dotm 0 0 1 172 983 UnB 8 1 1207 12.0 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--StartFragment-->We test the influence of the managerial quality thesis on organizational performance using a panel data set on 827 (out of 853) Brazilian municipalities of the state of Minas Gerais along a six year-period (2003-2008). The intra-country and intra-state comparison allows control for potential institutional, historical, and cultural variables. Local managerial quality is assessed in terms of mayoral education and experience (age and ex-mayor), and municipal performance is operationalized as property tax collected/capita and property tax collected as percentage of total tax revenue. The study covers the last two years of the (2001-2004) mayoral administration and the four years of the (2004-2008) administration. After testing the effect of political, economic and ideological and controlling for other municipal factors, contrary to our expectations, mayoral quality fails to explain property tax collection. On the contrary, political factors seem to explain municipal property tax collection. Specifically, compared to the first three years of mayoral administration, in the last year—that is during mayoral election year—municipalities tend to reduce their property tax collection. <!--EndFragment-->